STRATEGI SUKSES PENULISAN PENELITIAN TINDAKAN KELAS BAGI GURU SMA SANTA MARIA PEKANBARU - Teddy Chandra; Evelyn Wijaya; Stefani Chandra; Suyono Suyono; Andi Andi (LPPM Universitas Abdurrab, 2025)
Class Action Research (PTK) is a type of research carried out by teachers to improve learning practices in the classroom, create effective learning, and at the same time as an effort to increase teacher professionalism. The results of initial observations of research objects found that not all Santa Maria Pekanbaru High School teachers were able to design PTK due to a lack of understanding steps in carrying out PTK and procedures of writing scientific papers, lack of motivation and fighting power in carrying out PTK. PTK writing training activities at Santa Maria Pekanbaru High School will be held in March 2024 who attended of 48 participants. This PKM activity intended to provide information to teachers about the importance of PTK for teachers so that they can solve educational problems and will help improve the quality of education. This training includes several stages, namely planning, presentation of material and participants' discussion. The results of the service activities indicate that teachers understanding of PTK increases and have held discussions related to PTK topics where the final result is that there are 6 (six) teams of teachers who already have PTK topics.